Synthesis of nanostructured SnO2 as anode materials for lithium-ion batteries. - Low, Zhi Theng. (2010)
Tin(IV) Oxide (SnO2) nanostructures were synthesized by a simple hydrothermal method. First of all, the effect of reaction parameters such as precursor concentration, pH (both acidic and basic) concentration and ethanol/water solvent concentration on SnO2 nanostructures has been investigated. It was followed by the addition of surfactant and polymeric stabilizers which were found to have substantial effect on the shape and the uniformity of the products. Scanning electron microscopy (SEM) revealed different morphologies of the SnO2 nanoparticles synthesized, with most of them exhibited nanorod crystallites. Besides, X-ray diffraction (XRD) was carried out to identify tetrahedral rutile SnO2 crystal structure before and after calcinations. Brunauer-Emmett-Teller (BET) surface area measurement was also conducted to identify the absence of porous structures on the surface of SnO2 nanocrystals. Lastly, lithium-ion battery test revealed the electrochemical performance of the synthesized SnO2 nanoparticles. It was suggested that carbonization on the SnO2 samples could improve the lithium storage properties.